2018
DOI: 10.3389/fpls.2018.00917
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Consequences Induced by Epidermally-Located Anthocyanins in Young, Mature and Senescent Leaves of Prunus

Abstract: Anthocyanic morphs are generally less efficient in terms of carbon gain, but, in turn, are more photoprotected than anthocyanin-less ones. To date, mature leaves of different morphs or leaves at different developmental stages within the same species have generally been compared, whereas there is a lack of knowledge regarding different stages of development of red vs. green leaves. Leaves (1-, 7-, and 13-week-old) of red- (RLP) and green-leafed (GLP) Prunus in terms of photosynthetic rate, carbon metabolism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 92 publications
6
53
0
Order By: Relevance
“…Therefore, changes in sugar content and partitioning (Roessner et al 2006;Papadakis et al 2018), as well as in carbon skeleton devoted to aminoacids, which are strictly interlinked (Guo et al 2014) can be observed as a response to B excess (Sang et al 2015;Ayvaz et al 2016). An imbalance of C/N ratio also promote phenomena of early senescence (Lo Piccolo et al 2018;Sotiras et al 2019) and this explains the enhancement of senescence-related hormones i.e. jasmonic acid and ethylene promoted by B excess in barley and wheat (Öz et al 2009;Kayıhan et al 2017).…”
Section: Physiological and Biochemical Responses To B Excessmentioning
confidence: 99%
“…Therefore, changes in sugar content and partitioning (Roessner et al 2006;Papadakis et al 2018), as well as in carbon skeleton devoted to aminoacids, which are strictly interlinked (Guo et al 2014) can be observed as a response to B excess (Sang et al 2015;Ayvaz et al 2016). An imbalance of C/N ratio also promote phenomena of early senescence (Lo Piccolo et al 2018;Sotiras et al 2019) and this explains the enhancement of senescence-related hormones i.e. jasmonic acid and ethylene promoted by B excess in barley and wheat (Öz et al 2009;Kayıhan et al 2017).…”
Section: Physiological and Biochemical Responses To B Excessmentioning
confidence: 99%
“…Lo Piccolo et al (2018) found that the Chl content increased in mature leaves and significantly decreased toward the end of the experiment. These typical Chl content changes during lifespan of leaves were confirmed by many other authors (Lu et al 2001(Lu et al , 2002Weng et al 2005, Table 1.…”
Section: Discussionmentioning
confidence: 95%
“…4). Lo Piccolo et al (2018) found that anthocyanin content showed an inversed course of changes compared to Chl, but did not reach the values of juvenile leaves. However, we found that anthocyanins content both at the beginning and at the end of leaf lifespan were comparable and statistically insignificant (Fig.…”
Section: Day Fvmentioning
confidence: 95%
See 2 more Smart Citations